The complete guide to greener meetings and events - Goldblatt, Samuel (Wiley event management series, 2012)
While there are many reasons to incorporate sustainable practices into meetings and events, including saving costs and resources, protecting the environment, improving social issues, doing business more efficiently and effectively and attracting new audiences, the number one reason to go green is to do business better